Polyamide composition as well as preparation method and application thereof
By using a combination of long-chain aliphatic and semi-aromatic polyamides in the polyamide material and adding specific fillers to form a polyamide composition, the problem of deformation after bending of traditional plastic badmintons is solved, and the bending restoration performance and service life are significantly improved.
Patent Information
- Application Number
- CN202411992306.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
When traditional plastic badmintons are bent against external forces, they are prone to irreversible deformation or damage, which affects their effectiveness and life.
Long-chain aliphatic polyamide and semi-aromatic polyamide are combined with a specific composition, and a filler is added to form a polyamide composition. This composition is used as a badminton material to improve its bending and restoration performance.
It significantly improves the bending and resilience ability of badminton, extends its service life, and maintains a good appearance after bending fatigue without scaling.
Smart Images

Figure BDA0005223906670000091 
Figure BDA0005223906670000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a polyamide composition and a preparation method and application thereof. Background Art
[0002] Polyamide is the world's first synthetic fiber and is a general term for thermoplastic resins containing repeated amide groups on the main chain of the molecule. Polyamide has excellent mechanical properties and electrical insulation properties, high mechanical strength, good toughness, and excellent heat resistance, weather resistance and friction resistance, so it is widely used in the fields of automobiles, electronics, and consumer electronics.
[0003] When polyamide materials are used to make plastic badmintons, traditional plastic badmintons are often subjected to external forces, such as accidental bending, and often undergo irreversible deformation or damage, affecting their use effect and lifespan. Although plastic badmintons have improved durability and environmental adaptability compared to feather badmintons, their bending recovery performance still needs to be improved when facing extreme use conditions. Therefore, the development of a plastic badminton material with excellent bending recovery performance has become an urgent need in the industry. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a polyamide composition and a preparation method and application thereof. A "hard and soft" polyamide combination is compounded with a filler of a specific composition. The obtained polyamide composition can quickly restore its original shape after accidental bending. Using it as a badminton material can significantly improve the bending recovery ability of the badminton and maintain a longer service life.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a polyamide composition, which comprises the following components, in parts by weight: 45-75 parts of long-chain aliphatic polyamide, 5-20 parts of semi-aromatic polyamide and 0.5-7 parts of filler; the filler comprises a first filler and a second filler; the first filler comprises any one of talc, glass microspheres or barium sulfate, or a combination of at least two of them; the second filler comprises any one of calcium carbonate whiskers, calcium sulfate whiskers, wollastonite whiskers or potassium titanate whiskers, or a combination of at least two of them.
[0007] In the polyamide composition provided by the present invention, long-chain aliphatic nylon is used to improve the flexibility, performance retention rate and dimensional stability of the material, and semi-aromatic nylon is used to improve the rigidity of the material to prevent the material from being too soft and losing its recovery ability, thereby obtaining a polyamide composition with excellent bending recovery performance; further, by adding a filler of a specific composition and acting in combination with the polyamide, the deformation resistance effect is further enhanced, and at the same time, the material is guaranteed to have a good appearance after bending fatigue without peeling. The plastic badminton made of the polyamide composition has excellent durability, environmental adaptability and bending recovery, and the service life is extended.
[0008] Among them, the long-chain aliphatic polyamide is 45-75 parts, for example, it can be 45 parts, 46 parts, 48 parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, 60 parts, 62 parts, 64 parts, 66 parts, 68 parts, 70 parts, 72 parts, 74 parts, 76 parts, 78 parts, 80 parts, etc.; more preferably, it is 51-71 parts.
[0009] The semi-aromatic polyamide is 5-20 parts, for example, it can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc.; more preferably, it is 9-16 parts.
[0010] The filler is 0.5 to 7 parts, for example, 0.5, 0.6, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5, 5.2, 5.5, 5.8, 6, 6.2, 6.5, 6.8, 7, etc.; more preferably 1.5 to 4.5 parts.
[0011] As a preferred technical solution of the present invention, the mass percentage of long-chain aliphatic polyamide in the polyamide composition is ≥50%, for example, it can be 50%, 55%, 60%, 65%, 68%, 70%, 72%, 75%, 78%, 80% or 82%, etc.; more preferably, it is 65-85%.
[0012] As a preferred technical solution of the present invention, the mass percentage of the semi-aromatic polyamide in the polyamide composition is 10-22%, for example, it can be 11%, 13%, 15%, 17%, 19% or 21%.
[0013] As a preferred technical solution of the present invention, the mass percentage of filler in the polyamide composition is ≥0.5%, for example, it can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, etc.; more preferably, it is 1-5%.
[0014] Preferably, in parts by weight, the filler includes 0.05 to 5.5 parts of the first filler, for example, it can be 0.05 parts, 0.06 parts, 0.08 parts, 0.1 parts, 0.2 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.5 parts, 2.6 parts, 2.8 parts, 3 parts, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, 5 parts, 5.2 parts, 5.4 parts, 5.5 parts, etc.; more preferably, the content of the first filler is 0.5 to 2.5 parts.
[0015] Preferably, the first filler is selected from talc.
[0016] Preferably, the D50 particle size of the first filler is 1-10 μm, for example, 1.5 μm, 2 μm, 3 μm, 5 μm or 8 μm.
[0017] In the present invention, the D50 particle size can be measured by a laser particle size analyzer.
[0018] Preferably, in parts by weight, the filler includes 0.5 to 2.5 parts of the second filler, for example, it can be 0.05 parts, 0.06 parts, 0.08 parts, 0.1 parts, 0.2 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, etc.; more preferably, the content of the second filler is 0.5 to 2 parts.
[0019] In the present invention, the mass ratio of the first filler to the second filler is (0.05-5.5):1, wherein the specific value in (0.05-5.5) can be, for example, 0.05, 0.06, 0.08, 0.1, 0.2, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5 or a range between any of the above values.
[0020] Preferably, the second filler is selected from calcium carbonate whiskers.
[0021] Preferably, the second filler has a length of 20-30 μm, such as 21 μm, 23 μm, 25 μm, 27 μm or 29 μm, etc., and a diameter of 1-2 μm, such as 1.1 μm, 1.3 μm, 1.5 μm, 1.7 μm or 1.9 μm, etc.
[0022] In the present invention, the length and diameter of the second filler can be obtained by observation through a scanning electron microscope.
[0023] In the present invention, the second filler has a difference in force between the horizontal direction and the vertical direction, and forms a specific distribution with the first filler. The two work together to refine the crystal size of the material, improve the ability of the obtained polyamide composition to resist deformation, and further improve the bending recovery performance.
[0024] The combination of talcum powder and calcium carbonate whiskers is preferred. Due to the heterogeneous nucleation effect and the restriction on the movement of molecular chains, the nylon spherulites are unevenly distributed, which improves the material's ability to resist deformation. At the same time, the addition of talcum powder is conducive to the uniform dispersion and multi-dimensional orientation of calcium carbonate whiskers, showing a good synergistic effect.
[0025] Preferably, the viscosity of the long-chain aliphatic polyamide is 150-200 mL / g, for example, 155 mL / g, 160 mL / g, 165 mL / g, 170 mL / g, 180 mL / g or 190 mL / g.
[0026] In the present invention, the viscosity number is obtained by referring to ISO 307:2019 standard test.
[0027] Preferably, the long-chain aliphatic polyamide is obtained by co-polycondensation reaction or homo-polycondensation reaction.
[0028] Preferably, the molecular structure of the long-chain aliphatic polyamide comprises an aliphatic dibasic acid structural unit having a carbon number ≥10 (for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 22, 24, 26, 28, 30, etc.) and an aliphatic diamine structural unit having a carbon number ≥6 (for example, 6, 8, 10, 12, 14, 16, 18, 20, etc.); and / or, the molecular structure of the long-chain aliphatic polyamide comprises a structural unit derived from a cyclic lactam having a carbon number ≥10 (for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 22, 24, 26, 28, 30, etc.).
[0029] Preferably, the aliphatic dibasic acid having ≥10 carbon atoms is a straight-chain aliphatic dibasic acid.
[0030] Illustratively, the aliphatic dibasic acid having carbon atoms ≥ 10 includes any one of decanedioic acid, undecanedioic acid, dodecanedioic acid, tetradecanedioic acid, hexadecanedioic acid or octadecanedioic acid, or a combination of at least two thereof.
[0031] Preferably, the aliphatic diamine having carbon atoms ≥ 6 is a straight-chain aliphatic diamine.
[0032] Illustratively, the aliphatic diamine having carbon atoms ≥ 6 includes any one of hexamethylenediamine, heptamethylenediamine, octanediamine, nonamethylenediamine, decanediamine, undecanediamine, dodecanediamine, tetradecanediamine, hexadecanediamine or octadecanediamine, or a combination of at least two thereof.
[0033] Preferably, the long-chain aliphatic polyamide includes any one of polyhexamethylene sebacamide (PA610), polyhexamethylene dodecanediamine (PA612), polydecanediamine sebacamide (PA1010), polydecanediamine dodecanediamine (PA1012), polydodecanediamine dodecanediamine (PA1212), polyundecalactam (PA11) or polydodecanediamine (PA12), or a combination of at least two thereof.
[0034] Preferably, the viscosity of the semi-aromatic polyamide is 150-200 mL / g, for example, 155 mL / g, 160 mL / g, 165 mL / g, 170 mL / g, 180 mL / g or 190 mL / g.
[0035] In the present invention, the viscosity number is obtained by referring to ISO 307:2019 standard test.
[0036] Preferably, the molecular structure of the semi-aromatic polyamide comprises an aromatic dibasic acid structural unit and an aliphatic diamine structural unit having a carbon number ≥ 2 (for example, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, etc.), and / or a combination of an aromatic diamine structural unit and an aliphatic dibasic acid structural unit having a carbon number ≥ 2 (for example, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, etc.).
[0037] Illustratively, the aromatic dibasic acid includes any one of isophthalic acid, isophthalic acid, terephthalic acid or terephthalic acid or a combination of at least two thereof.
[0038] Exemplarily, the aliphatic diamine having a carbon number ≥ 2 includes any one of ethylenediamine, propylenediamine, butylenediamine, pentanediamine, hexamethylenediamine, heptanediamine, octanediamine, nonanediamine, decanediamine, undecanediamine, dodecanediamine, tetradecanediamine, hexadecanediamine or octadecanediamine, or a combination of at least two thereof.
[0039] Illustratively, the aromatic diamine includes any one of meta-phenylenediamine, meta-phenylenediamine, para-phenylenediamine or a combination of at least two of para-phenylenediamine.
[0040] Illustratively, the aliphatic dibasic acid having a carbon number ≥ 2 includes any one of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tetradecanedioic acid, hexadecanedioic acid or octadecanedioic acid, or a combination of at least two thereof.
[0041] Preferably, the semi-aromatic polyamide includes any one of poly(m-phenylene diamine) adipate (PA MXD6), poly(hexamethylene isophthalamide) (PA6I), poly(hexamethylene terephthalamide) (PA6T), poly(decamethylene terephthalamide) (PA10T) or poly(terephthalic acid / hexamethylene isophthalamide) (PA6I6T) or a combination of at least two thereof.
[0042] Preferably, the long carbon chain polyamide composition further comprises 2-8 parts of a toughening agent, for example, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 5 parts, 6 parts or 7 parts.
[0043] Preferably, the toughening agent includes any one of maleic anhydride grafted octene ethylene copolymer and maleic anhydride grafted ethylene propylene diene rubber or a combination of at least two thereof, and more preferably maleic anhydride grafted octene ethylene copolymer.
[0044] In a second aspect, the present invention provides a method for preparing the polyamide composition as described in the first aspect, characterized in that the preparation method comprises the following steps:
[0045] The polyamide composition is obtained by mixing long-chain aliphatic polyamide, semi-aromatic polyamide, filler and optional toughening agent, and then extruding and granulating.
[0046] Preferably, the extrusion granulation is carried out in a twin-screw extruder.
[0047] Preferably, the screw aspect ratio of the twin-screw extruder is (36-48):1, wherein the specific value of (36-48) can be, for example, 37, 38, 40, 42, 44 or 46.
[0048] Preferably, the barrel temperature of the twin-screw extruder is 220-280°C, for example, 230°C, 240°C, 250°C, 260°C or 270°C.
[0049] Preferably, the screw speed of the twin-screw extruder is 200-350 rpm, for example, it can be 220 rpm, 250 rpm, 280 rpm, 300 rpm or 320 rpm.
[0050] In a third aspect, the present invention provides a badminton shuttlecock, wherein the material of the badminton shuttlecock comprises the polyamide composition as described in the first aspect.
[0051] In the present invention, the polyamide composition is used to prepare the feathers of the badminton shuttlecock.
[0052] Compared with the prior art, the present invention has at least the following beneficial effects:
[0053] The present invention provides a polyamide composition, a preparation method and application thereof. By combining long-chain aliphatic polyamide and semi-aromatic polyamide, the bending recovery performance of the material is improved. By further adding fillers of a specific composition for compounding, the crystal size of the material is refined and its ability to resist deformation is improved. The polyamide composition provided by the present invention is used as a badminton material, which can significantly improve the application performance and extend the service life. DETAILED DESCRIPTION
[0054] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0055] In the following specific implementation of the present invention, the materials involved are as follows:
[0056] (1) Long-chain aliphatic polyamide
[0057] PA12, VESATAMID L194, Yingchuang, Germany, viscosity number is 180mL / g;
[0058] PA1012, RV29.5, Shanghai Yinggu, viscosity number is 190mL / g.
[0059] PA66: ST801NC010A, Yuanbang New Materials.
[0060] (2) Semi-aromatic polyamide
[0061] PA6I6T, TI1207, Shandong Guangyin, viscosity number is 200mL / g;
[0062] PAXMD6, M30m, Shanghai Yinggu, viscosity number is 150mL / g.
[0063] (3) First filler
[0064] Talc, HTPULTRA5L, Liaoning Aihaiyimi, D50 particle size 3μm;
[0065] Barium sulfate, HD-8000, Yichang Hengda Chemical, D50 particle size is 3 μm.
[0066] Mica powder: Chuzhou Baota Sericite Mining Co., Ltd. GW-4 type, 3000 mesh.
[0067] (4) Second filler
[0068] Calcium carbonate whiskers, NP-CW2, Shanghai Fengzhu, length 25 μm, diameter 1.5 μm;
[0069] Calcium sulfate whiskers, NP-S04-S, Shanghai Fengzhu, length 30 μm, diameter 2 μm.
[0070] (5) Toughening agent
[0071] Maleic anhydride grafted ethylene-octene copolymer, KT-915, Shenyang Ketong.
[0072] Example 1
[0073] A polyamide composition comprises, by weight, 50 parts of PA12, 10 parts of PA6I6T, 1 part of talc, 1 part of calcium carbonate whisker and 2 parts of maleic anhydride grafted ethylene-octene copolymer.
[0074] The polyamide composition is prepared by the following method:
[0075] After weighing each component according to a ratio and premixing, the components are put into a twin-screw extruder for melt blending, extrusion granulation, and obtaining the polyamide composition;
[0076] The screw length-to-diameter ratio of the twin-screw extruder is 40:1, the temperature of each section of the screw barrel is set to 270℃-250℃-250℃-250℃-250℃-250℃-260℃-280℃ in sequence, and the screw speed is 200rpm.
[0077] The following performance tests were performed on the polyamide composition provided in Example 1:
[0078] (1) Bending fatigue appearance
[0079] The obtained polyamide composition is injection molded into a 100*10*1mm specimen, and the specimen is vertically fixed at the inlet A end, and the distal B end of the gate is bent 90 degrees and then restored. The bending is repeated 20 times to observe whether the appearance of the bent area is peeling, breaking, wrinkling, whitening, etc. If there is no peeling, breaking, wrinkling, or whitening, it is judged to be "excellent".
[0080] (2) Bending recovery angle
[0081] The obtained polyamide composition was injection molded into a 100*10*1mm spline, the A end of the spline was vertically fixed, the B end was bent 100 degrees, and the spline was allowed to recover naturally. The angle difference between the spline and the original position was tested. The larger the angle, the worse the bending recovery.
[0082] (3) Flexural modulus
[0083] The flexural modulus is tested according to the relevant standard of ISO 178-2019.
[0084] (4) Izod notched impact strength
[0085] The Izod notched impact strength is tested according to the relevant standards of ISO 180-2023.
[0086] The test results are summarized in Table 1.
[0087] Examples 2-8, Comparative Examples 1-8
[0088] A polyamide composition, which differs from Example 1 in that the formula of the polyamide composition is different, as shown in Table 1 and Table 2; wherein the dosage unit of each component is "parts by weight" of the solid content; the preparation method and performance testing method of the polyamide composition are the same as those of Example 1.
[0089] Table 1
[0090]
[0091] Table 2
[0092]
[0093] It can be seen from the test results that the present invention obtains a polyamide composition with a bending recovery angle as low as less than 3° by compounding a combination of specific polyamide materials with fillers of specific composition, and the morphology after bending is good. In some preferred technical schemes, there is no peeling, breakage, wrinkling or whitening, which significantly improves the bending recovery performance of the polyamide composition and meets its application requirements as a plastic badminton.
[0094] By comparing Example 1 with Examples 5 and 6, it can be seen that the present invention significantly improves the bending modulus and impact strength of the polyamide composition by further utilizing the synergistic effect of talcum powder and calcium carbonate whiskers, thereby obtaining better mechanical properties.
[0095] By comparing Example 1 with Examples 7 and 8, it can be seen that the polyamide composition prepared by the present invention can achieve better bending resistance, rigidity and impact performance by using the first filler and the second filler with specific contents.
[0096] By comparing Example 1 with Comparative Examples 1, 3, 4, and 8, it can be seen that the present invention further improves the bending recovery performance and mechanical strength of the material by adopting a combination of a specific first filler and a specific second filler.
[0097] By comparing Example 1 with Comparative Examples 2, 5-7, it can be seen that the present invention improves the bending resistance and flexural modulus of the composition by compounding long-chain aliphatic polyamide with semi-aromatic polyamide. The applicant declares that the above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the protection scope and disclosure scope of the present invention.
Claims
1. A polyamide composition, characterized in that The polyamide composition comprises the following components in parts by weight: 45-75 parts of long-chain aliphatic polyamide, 5-20 parts of semi-aromatic polyamide and 0.5-7 parts of filler; The filler includes a first filler and a second filler; The first filler comprises any one of talc, glass microspheres or barium sulfate, or a combination of at least two thereof; The second filler includes any one of calcium carbonate whiskers, calcium sulfate whiskers, wollastonite whiskers or potassium titanate whiskers, or a combination of at least two of them.
2. The polyamide composition according to claim 1, characterized in that In parts by weight, the filler includes 0.05 to 5.5 parts of the first filler, and more preferably the content of the first filler is 0.5 to 2.5 parts; Preferably, the first filler is selected from talc; Preferably, the D50 particle size of the first filler is 1-10 μm.
3. The polyamide composition according to claim 1 or 2, characterized in that In parts by weight, the filler includes 0.05 to 2.5 parts of the second filler, and more preferably the content of the second filler is 0.5 to 2 parts; Preferably, the second filler is selected from calcium carbonate whiskers; Preferably, the second filler has a length of 20-30 μm and a diameter of 1-2 μm.
4. The polyamide composition according to claim 1, characterized in that The viscosity of the long-chain aliphatic polyamide is 150-200 mL / g; Preferably, the molecular structure of the long-chain aliphatic polyamide comprises an aliphatic dibasic acid structural unit having ≥10 carbon atoms and an aliphatic diamine structural unit having ≥6 carbon atoms; and / or, the molecular structure of the long-chain aliphatic polyamide comprises a structural unit derived from a cyclic lactam having ≥10 carbon atoms; Preferably, the long-chain aliphatic polyamide includes any one of polyhexamethylene sebacamide, polyhexamethylene dodecane diamide, polydecanediamine sebacamide, polydecanediamine dodecane diamide, polydodecane diamide, polyundecanediamine, or polylauryllactam, or a combination of at least two thereof.
5. The polyamide composition according to claim 1, characterized in that The viscosity of the semi-aromatic polyamide is 150-200 mL / g; Preferably, the molecular structure of the semi-aromatic polyamide comprises an aromatic dibasic acid structural unit and an aliphatic diamine structural unit having a carbon number ≥ 2, and / or comprises a combination of an aromatic diamine structural unit and an aliphatic dibasic acid structural unit having a carbon number ≥ 2; Preferably, the semi-aromatic polyamide includes any one of poly(isophthalic acid)-adipate, poly(hexamethylene isophthalamide), poly(hexamethylene terephthalamide), poly(decamethylene terephthalamide) or poly(terephthalic acid / isophthalic acid)-hexamethylene diamine, or a combination of at least two thereof.
6. The polyamide composition according to claim 1, characterized in that The polyamide composition further comprises 2-8 parts of a toughening agent in parts by weight; Preferably, the toughening agent includes any one of maleic anhydride grafted octene ethylene copolymer and maleic anhydride grafted ethylene propylene diene rubber or a combination of at least two thereof, and more preferably maleic anhydride grafted octene ethylene copolymer.
7. A method for preparing a polyamide composition according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: The polyamide composition is obtained by mixing long-chain aliphatic polyamide, semi-aromatic polyamide, filler and optional toughening agent, and then extruding and granulating.
8. The preparation method according to claim 7, characterized in that: The extrusion granulation is carried out in a twin-screw extruder; Preferably, the screw aspect ratio of the twin-screw extruder is (36-48):1; Preferably, the barrel temperature of the twin-screw extruder is 220-280°C; Preferably, the screw speed of the twin-screw extruder is 200-350 rpm.
9. A badminton, characterized in that: The material of the badminton shuttlecock comprises the polyamide composition according to any one of claims 1-7.
10. The badminton according to claim 9, characterized in that: The polyamide composition is used for preparing the feathers of the badminton shuttlecock.
Citation Information
Cited By
Polyamide composition as well as preparation method and application thereof
CN121554954A